Early internationalization: The importance of skills and relational networks - Lobo, Carla Azevedo (2017)
Companies are currently required to continually innovate and restructure their operations in order to respond to the requirements of national and international competition. Companies have to find new ways to develop competitive advantages and acquire new skills, resources and capabilities. Since the 90’s, the research on international new ventures (INV) contested the idea that new or small companies can’t be early internationalized or that they would only do so incrementally. Since then, a growing flow of research into international new ventures has tried to understand the causes, processes, and outcomes of the decision to early enter foreign markets. A common thread concerns the role of learning and knowledge. Organizational knowledge, or its absence, was a central explanation for internationalization in original stage-based models (Uppsala School), but INV theory recognized that individual factors such as international experience can also influence the pace and specially the beginning of internationalization. More specifically, some recent empirical evidence offers important insights into the internationalization of new business, showing that younger companies are able to compensate for their limited experiential learning through previous individual experiences of the top management team and through inter-organizational relationships. Based on our literature review we intend to evaluate entrepreneurs’ opinions, in order to ascertain whether factors such as a relational network, worker’s specific skills and "worker’s international experience, can act as enhancing agents or inducers of the company internationalization process. Moreover we intend to investigate if there are differences in the importance of these factors to those companies that internationalize early in their life cycle (maturity level). An empirical study was carried out with 320 Portuguese companies through Exploratory Analysis and Univariate Statistical Inference methodologies. We found evidence that allows us to say that companies that internationalize early in their life cycle are those which most value the importance of worker’s specific skills and worker’s international experience. However relational networks don’t depend on companies’ maturity level.Keywords: Internationalization, skills, networks.